A development of an informative web based kiosk for Kampung Jenjarom, Kuala Langat Selangor / Noridawati Zakaria - Zakaria, Noridawati (2005)
The number and range of university of adapting and developing a website as their tools to provide and distribute information is growing rapidly. These websites are the tools to provide education information also called as collaboration to their students, lecturer's staffs and visitors. These websites are commonly use by various university in Malaysia as their tools. As the growing era technology, the term of virtual tour existed in the website usage. This term shows that the user can feel the environment of real world in their viewing website from anywhere also called as simulation of real world. Based on this experience using website as collaboration tools, the usage can be enhanced to presentation of information in virtual tour form through the research where user can view several area of Kampung Jenjarom at Kuala Langat Selangor in panoramic image view (360°) and can view the village information directly from this website. The analysis was carried out, a design and preliminary implementation of a prototype is developed. Experience from the trial of the system shows that the virtual village concept brought through this website is more cost effective and wonderful to develop.